Analiza zmian na rynku papierów komercyjnych w Polsce - Pauka, Marek (Analysis of Changes on the Commercial Paper Market in Poland, 2006)
There has been a downward trend on the nonpublic short-term debt securities in Poland in the last three years. The author conducts quantity analysis of the changes on the commercial paper market and identifies the phases of its development. He also makes some effort to find factors which influence the market today and in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 456-464